Kriteria Pemilihan Tapak pada Perancangan Sport Science Center di Surabaya - Faramayla Adinda Rinaldy; Andarita Rolalisasi; Febby Rahmatullah Masruchin (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Surabaya is one of the metropolitan cities in Indonesia with significant potential for the development of sports performance and the improvement of public health quality. The advancement of modern sports requires a sport science–based approach that integrates training, health, technology, and research aspects. However, the lack of integrated sport science facilities remains a major challenge. Therefore, proper site selection is a crucial factor in the design of a Sport Science Center. This study aims to formulate appropriate site selection criteria for the design of a Sport Science Center in Surabaya. The research method used is descriptive qualitative, employing literature studies, site observations, and comparative analysis of alternative sites based on predetermined criteria. The results indicate that the main site selection criteria include accessibility, proximity to supporting facilities, compliance with spatial planning regulations, environmental conditions, land area, and future development potential. Based on the analysis, the Middle East Ring Road (MERR) area in Surabaya is considered the most suitable location for the development of a Sport Science Center.